Amygdala subregional functional connectivity in treatment-resistant depression - Sheryl L. Foster; Ramon Landin-Romero; Sarah Lewis; Ana Rita Barreiros; Sophie Matis; Anthony Harris; Mayuresh S. Korgaonkar (Journal of Affective Disorders Reports)
Background: Treatment resistance impacts almost 50 % of depression patients, with amygdala dysfunction being widely implicated. fMRI studies have typically focussed on identifying whole rather than individual subregional amygdala functional connectivity but this approach, together with cohort heterogeneity, is likely contributing to inconsistent results. This study used high resolution 3T fMRI data to investigate subregional alterations that may differentiate treatment-resistant cohorts from healthy individuals and depressed patients who respond to treatment. Methods: Resting-state fMRI data were obtained in 35 participants diagnosed with Treatment-Resistant Depression (TRD), 38 healthy control participants (HC), and 35 treatment-sensitive participants (TSD). Seed-based functional connectivity analyses of three main subregions bilaterally (laterobasal, centromedial and superficial), as well as the whole amygdala, were performed and comparisons made between groups. Results: We found connectivity differences in the right laterobasal amygdala subregion in TRD compared to both groups. TRD patients displayed hypoconnectivity to the right fusiform gyrus relative to HC whereas hyperconnectivity to the left inferior frontal gyrus relative to TSD was identified. No connectivity differences were found for the whole amygdala or any of the other subregions bilaterally. Limitations: Modest sample size and cross-sectional study design are limitations. A causal relationship between functional connectivity alterations and treatment resistance cannot be established. Conclusion: Altered connectivity of the right laterobasal subregion is a distinguishing feature of TRD. These alterations may underlie severe impairments in emotion processing and social functioning that are characteristic of TRD. These results emphasise the need for further investigation of the functional role of the amygdala subregions in depression.